The Effectiveness of Marathon Technique in Improving Students' Descriptive Writing - Vadia, Mila Nur; Mutiarani, Mutiarani (La Ogi : English Language Journal, 2024)
This research was aimed to investigate whether or not Marathon technique gave impact on students’ descriptive writing improvement. This research applied quantitative method with quasi-experimental research design. A total of 40 students of grade 9 of MTs Al-Islamiyah, Ciledug, participated as the samples in which 20 students were in the experimental class and the other 20 in controlled class. Both pretest and posttest were used as the instruments to collect the data. These data were analyzed statistically by using paired-sample t-test. The results of this statistical calculation showed that (t0) > than (tt) = 2.81 > 1.76 in the significance level of 5%. This explained that there was significant difference gained by groups of students taught with and without using Marathon technique. Therefore, this research concluded that Marathon technique affected students’ descriptive text writing achievement.